Alternative Routes to Induce Naïve Pluripotency in Human Embryonic Stem Cells - Duggal, Galbha; Warrier, Sharat; Ghimire, Sabitri; Broekaert, Dorien; Van der Jeught, Margot; Lierman, Sylvie; Deroo, Tom; Peelman, Luc; Van Soom, Ann; Cornelissen, Ria; Menten, Björn; Mestdagh, Pieter; et al. (Stem cells (Dayton, Ohio), 2015)
Human embryonic stem cells (hESCs) closely resemble mouse epiblast stem cells exhibiting primed pluripotency unlike mouse ESCs (mESCs), which acquire a naïve pluripotent state. Efforts have been made to trigger naïve pluripotency in hESCs for subsequent unbiased lineage‐specific differentiation, a common conundrum faced by primed pluripotent hESCs due to heterogeneity in gene expression existing within and between hESC lines. This required either ectopic expression of naïve genes such as NANOG and KLF2 or inclusion of multiple pluripotency‐associated factors. We report here a novel combination of small molecules and growth factors in culture medium (2i/LIF/basic fibroblast growth factor + Ascorbic Acid + Forskolin) facilitating rapid induction of transgene‐free naïve pluripotency in hESCs, as well as in mESCs, which has not been shown earlier. The converted naïve hESCs survived long‐term single‐cell passaging, maintained a normal karyotype, upregulated naïve pluripotency genes, and exhibited dependence on signaling pathways similar to naïve mESCs. Moreover, they undergo global DNA demethylation and show a distinctive long noncoding RNA profile. We propose that in our medium, the FGF signaling pathway via PI3K/AKT/mTORC induced the conversion of primed hESCs toward naïve pluripotency. Collectively, we demonstrate an alternate route to capture naïve pluripotency in hESCs that is fast, reproducible, supports naïve mESC derivation, and allows efficient differentiation. Stem Cells 2015;33:2686–2698 Different Shades of Naïve Pluripotency in Human Embryonic Stem Cells.